Is a first-trimester subchorionic hematoma and its size a risk for preterm premature rupture of membranes? (Annals of Medical Research, 2022)
Aim: To assess the relationship between first-trimester subchorionic hematoma (SCH) size and preterm premature rupture of membranes (PPROM).Materials and Methods: In this retrospective study, we included patients with a singleton intrauterine pregnancy between 5 and 14 gestational weeks. After analyzing the 1,440 pregnant women who applied for inclusion in the study based on vaginal bleeding during their first trimester, we found that 228 had SCH. After excluding those who had miscarried before viability and who had complicated pregnancies, 186 remained who were included in the final analysis. The SCH group was subdivided into three groups according to hematoma size as follows: mild (n: 62), moderate (n: 56), and severe SCH (n: 68). The severity of SCH was calculated according to the ratio of the gestational sac length to the linear length of the bleeding area.Results: Maternal demographic characteristics were similar among the groups. The gestational age at delivery was significantly lower in the severe SCH group than in the other groups. The fetal birth weight was significantly lower in the severe SCH group than in the other groups. PPROM rates were significantly higher in the severe SCH compared to mild SCH, moderate SCH and control group.Conclusion: Our data suggest that the presence of a first-trimester mild or moderate SCH in singleton pregnancies is not associated PPROM, but that severe SCH is associated with PPROM.
Keywords: preterm prelabor rupture of membranes; PPROM; subchorionic hematoma; SCH; adverse neonatal morbidity